(untitled) (Architecture Image Studies, 2025)
This study investigates the collaborative governance model in risk-based business licensing services (OSSRBA) at the Investment and One-Stop Integrated Services Department (DPMPTSP) of Bandung City. The research is grounded in the substantive alignment between collaborative governance principles and the multi-stakeholder nature of licensing services. Employing Emerson et al.’s (2012) theory, which encompasses system context, drivers, and collaborative dynamics, this qualitative case study analyzes OSSRBA implementation. Findings indicate that while the system context (legal framework) and drivers (demand for ease of doing business) have established a conducive environment, the collaborative dynamics dimension, particularly capacity for joint action, remains significantly underdeveloped. This manifests as fragmented coordination, inadequate human resource preparedness, and unintegrated systems and data, hindering OSSRBA’s effectiveness. The study addresses a critical academic gap by deeply dissecting the dynamic and relational processes among actors, moving beyond mere policy output evaluation. It proposes a contextual collaborative governance model emphasizing integrated coordination, HR development, and digital infrastructure to enhance OSSRBA implementation, offering theoretical contributions to bureaucracy reform and practical policy recommendations for local governments.